Analyzing the Effectiveness of Vocational Education in Enhancing Employability and Skill Development: A Domain-Based Quantitative Study - Dr. Sumera Imran; Dr. Sara Rafiq; *Dr. Zahid Ullah; Bushra (Social Science Review Archives, 2025)
In Malakand Division of Khyber Pakhtunkhwa, Pakistan, female participation in the labor market remains limited due to socio-cultural constraints, restricted access to skills training, and weak linkages between education and employment. Technical and Vocational Education and Training (TVET) is increasingly viewed as a viable pathway for enhancing women’s employability and economic empowerment in the region. However, empirical evidence examining the effectiveness of vocational education for female graduates across multiple skill domains remains scarce. This study analyzes the effectiveness of vocational education in enhancing employability and skill development among female TVET graduates in Malakand. Vocational education is widely regarded as a strategic mechanism for addressing skills shortages and improving graduate employability; however, empirical evidence regarding its effectiveness across multiple skill domains remains limited. This study analyzes the effectiveness of vocational education in enhancing employability and skill development using a domain-based quantitative approach. A cross-sectional survey design was employed, and data were collected from 200 graduates of vocational education institutions using a structured questionnaire. Ten key domains technical skills, soft skills, job readiness, practical training exposure, curriculum relevance, industry linkages, digital skills, problem-solving skills, career awareness, and employability were examined. The findings reveal that vocational education significantly enhances technical skills, curriculum relevance, and job readiness, while comparatively lower outcomes were observed in soft skills, industry linkages, and career awareness. Analysis showed that job readiness and practical training exposure were the strongest predictors of employability, explaining a substantial proportion of variance in employment outcomes. The study provides robust empirical evidence supporting the effectiveness of vocational education while highlighting critical areas for improvement. The findings indicate that vocational education significantly enhances technical skills, curriculum relevance, and job readiness among female graduates in Malakand. However, comparatively lower mean scores were observed in soft skills, industry linkages, career awareness, and digital skills, reflecting contextual and structural challenges faced by women in accessing employment opportunities. The findings have important implications for policymakers, educators, and training institutions seeking to strengthen vocational education systems and improve graduate employability.